How Readers Process Complex Literary Texts - Mackey, Margaret ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
Reading is invisible. Any report of another's reading (beyond the level of word recognition) must rely on some kind of reproduction of the actual experience; there is no way to tap into the experience itself. After completing a pilot study, a small number of adolescents--5 eighth graders and 5 eleventh graders read the first four chapters of Gillian Cross'"Wolf" and later took the book home to finish reading it. Then, meeting again with the researcher, they worked through these chapters a second time, and finally, they discussed the book as a whole. Results focused on how readers decide if their interpretations of the text are "good enough," a value growing out of a student's own individual balance between momentum and accountability, or in other words, between their need for pace and their need to understand. Some readers have a bias towards momentum and go with the flow of the text, while others have a bias towards accountability and are more careful to understand every detail before going on. A detailed accounting shows how three students in particular wrestled with the problem of "good enough." And one specific issue arose in discussion with the readers--the question of re-reading. Conclusions focus on the triangular tension between the reader's personal experience of the text, the text itself, and the experience others have in reading a text. (Contains 10 references.) (TB)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (San Francisco, CA, April 18-22, 1995).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Discussion; Foreign Countries; Grade 11.; Grade 8.; Reader Response; Reader Text Relationship; Reading Habits; Reading Processes; Reading Research; Reading Strategies; Secondary Education; Reading Behavior -- Text Processing (Reading); Opinion Papers; Speeches/Meeting Papers; Reports, Research